2016
DOI: 10.18517/ijaseit.6.6.1508
|View full text |Cite
|
Sign up to set email alerts
|

The Decoding of Traffic Signs by Motorcycle Riders in Jakarta Indonesia

Abstract: Should the rapid growth of motor vehicles and inhabitants goes unanticipated, it is certain that the motor vehicles pacing in JABODETABEK area will significantly decelerate. The problem of clogging in Jakarta is not only due to the ever-increasing number of motor vehicles and minimum development of streets but also to the behavior of road users. The behavior of road users is vital in solving the problems in transportation such as clogging or traffic safety like the circumstances in Jakarta today. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Thus, risk mitigation procedure may reduce the toll project risks in a systematic procedure. Furthermore, the positive impacts in the implementation of this toll road complete with adequate traffic signs, road markings, safety devices, smart devices (for example Smart Payment Systems) may also reduce traffic congestion, air pollution, and traffic accidents [33], [34], [35]. Hence, by the implementation a systematic risk management procedure and the improvement of road infrastructure and facilities, hence these efforts ultimately may save many life as well as public money [36], [37].…”
Section: 99mentioning
confidence: 99%
“…Thus, risk mitigation procedure may reduce the toll project risks in a systematic procedure. Furthermore, the positive impacts in the implementation of this toll road complete with adequate traffic signs, road markings, safety devices, smart devices (for example Smart Payment Systems) may also reduce traffic congestion, air pollution, and traffic accidents [33], [34], [35]. Hence, by the implementation a systematic risk management procedure and the improvement of road infrastructure and facilities, hence these efforts ultimately may save many life as well as public money [36], [37].…”
Section: 99mentioning
confidence: 99%
“…Moreover, combination and adjustment of road signs, context and laws can make the drivers avoid ambiguous situations and doubtful decision-making, and then automatically subject the drivers to compliance with applicable laws (Bazire & Tijus, 2009). Violations of traffic signs occurs because of the human errors in understanding the meaning of signs, indifference to signs and the weakness supervision and enforcement of traffic laws (Winarso, 2016). A combination of poor traffic rules knowledge, a tendency to speed, an inability to control emotions and focus on driving can lead to someone violating traffic rules (Lady et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the previous study based on subjective interview to local Indonesian drivers about the behavior of road users (Winarso, 2016), it can be concluded that the violation and ignorance of the traffic signs, road markings, and traffic signal devices were stimulated by internal, external and other factors. The internal factor described as the needs to get to the destination as soon as possible.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations